Perceived implications of COVID-19 policy measures on food insecurity among urban residents in Blantyre Malawi - Mastano N. Dzimbiri; Patrick Mwanjawala; Emmanuel Chilanga; George N. Chidimbah Munthali (BMC, 2022)
Abstract Background Malawi is at the brink of experiencing food insecurity amidst the COVID-19 pandemic as the vast majority of its population lives in extreme poverty. While measures are being implemented to avert the spread of COVID-19, little is known about how COVID-19 policy measures have impacted food insecurity in urban Malawi. This study addresses this gap by exploring the implications of COVID-19 policy measures on food insecurity in low-income areas of Blantyre in Malawi. Methods We used Bronfenbrenner's ecological theory to explore the implications of COVID-19 policy measures on peoples' access to food. In-depth interviews were conducted with fifteen participants comprising of private school teachers, street vendors, sex workers, and minibus drivers. Data were analyzed using thematic analysis in which emerging patterns and themes from the transcripts were identified. Results The COVID-19 lockdown measures undermined participants' ability to maintain livelihoods. These measures have increased the vulnerability of the residents to food insecurity, forcing them to face severe challenges to accessing adequate food to support their families as a result of low incomes, job loss, and business disruptions. Conclusion Our study underscores the need for the Malawi government to seriously consider the provision of basic necessities such as food to the urban poor. We also suggest that the Malawi government should continue and expand the social cash transfer or relief funding packages by targeting the most vulnerable groups in the city. There is also a need for the government to engage all stakeholders and work collaboratively with people at local level in policymaking decisions in times of crisis.